The literary facets of the Qur'an as a guideline for islamic literary writing - Ahmad H.Osman, Rahmah (ISTAC, 2014)
The Islamic theory of literature and its practices are studied in the context of Qur’anic examples. As the Qur’an is a comprehensive guideline to life, and considers the human soul, feelings, thoughts and actions, it gives basic rules and outline to Islamize the literature. Muslim scholars have discussed the Islamic literature based on the stories in the Qur’an and the way of its narration. The Qur’an does not define Islamic literature, however it provides rules and outline through the examples contesting both form and content to the extent of maintaining complete musical effect. Islamic literature has been developed by Muslim scholars, based on this Qur’anic concepts and the style in which it presents its message. Thus, Islamic literature not only carries ethics and values but also addresses the basic human needs and feelings for enjoyment and pleasure.